Research commercialization scorecard a model for the evaluation of government-funded R&D slated for commercialization - Hipol, Karen Ann U. author (University of the Philippines Diliman, Quezon City Technology Management Center, 2009)
The weakest link in the Philippine innovation system is the process of transferring and commercializing the results of research and development, particularly those undertaken by government-funded R&D institutions. The slow pace of technology commercialization is demonstrated by the low number of patents, licenses and revenues generated in the country; particularly when compared to those of our ASEAN neighbors. This study focuses on two factors that contribute to the speed of technological innovation of government funded R&D : the government funds allocated for development projects-- projects that involve proof of concept, prototyping and pilot testing which are necessary prior to commercialization; and the criteria and evaluation procedures used to determine the commercial viability of such projects before they are approved for funding. The study also examines two government institutes that provide funds for development research, the Department of Science and Technology-Technology Innovation for Commercialization Program (TECHNICOM) and the Department of Agriculture Philippine Rice Research Institute (PhilRice). While there is a limited number of government funds specifically allocated for development projects, these funds are not fully liquidated. It could be the lack of a commercial/market mindset and not limited funds that is the leading cause of the dearth of development projects in technology. The sources of development funds, specifically those of DOST-TECHNICOM should be well-marketed to the private sector. They should target to finance development projects that would provide high impact to vital industries, and produce platform technologies that would lead not only to one, but to several new products.
While the number of actual market success of DOST-TECHNICOM is limited, the scheme of DOST-TECHNICOM shows that it is working. The requirement of having a private sector counterpart for funded projects is a safeguard that ensures the possibility of commercialization. New safeguards could include the assurance of next-level financing and evaluation of technical and commercial potential by outside experts. PhilRice demonstrates that when the prospect of commercialization is present at the conception of any research activity and when specific questions about the commercial potential of a project is asked, the probability of success is greater. However, PhilRice should analyze and monitor the percentage of its R&D budget that is spent on development projects. This may indicate the need to allocate the funds for development projects per se. After a review of the different funding sources in the Philippines, and the criteria used by professional financiers and government institutes around the world, this paper outlines a Research Commercialization Scorecard. This proposed scorecard can be used by government agencies when selecting or prioritizing projects for development and commercialization. It incorporates elements that are important to the private sector such as : scientific and technical feasibility, importance of the problem, commercial potential, project team, project management, and network partners. Government institutes must review their current criteria and common factors in successful projects and combine this with the proposed scorecard. While the suggested elements of the scorecard are essential, each institute should still develop their own metrics. The best practices and criteria used by private firms and professional financiers for project evaluation are well documented. Government funding agencies should incorporate these practices and criteria in their own processes in order to increase the likelihood of private sector commercialization.
In partial fulfillment of the requirements in TM 299.2
Keywords: Research Commercialization Scorecard